Affective activism: answering institutional productions of precarity in the corporate university - Adsit, Janelle, author; Doe, Sue, author; Allison, Marisa, author; Maggio, Paula, author; Maisto, Maria, author; Johns Hopkins University Press, publisher (Colorado State University. Libraries, 2015)
Given the context in which precarity is unevenly distributed in today's corporate university, it is important for women's studies to consider its role in bringing about higher education policy reform. Reporting on the findings of a national survey of chairs and directors of women's studies departments, this article suggests strategies for performing "affective activism" within the university through research and action, guided by feminist theory—including collaborative organic theater, institutional discourse analysis, and the drafting of position statements. Drawing from a range of experiential and discursive primary-source materials, the essay suggests strategies and examples for how institutional norms can be made available for interrogation and transformation. In this work, emotion can provide a lens by which to see the institutional situation of women's studies and its intervention in the new status quo of the corporate university.
Keywords: adjunct faculty; contingency; discourse; gender equity; managerialism; precarity; tenure; women faculty